Gricean Cooperative Principle and Conversational Implicature in Prabowo Subianto`s United Nations General Assembly Speech : a Pragmatic Analusis of Idiological Positioning - Muharram, Frisky; Sulistyaningsih, Sulistyaningsih (Journal of Industrial Engineering & Management Research, 2026)
This study examines the realization of Grice’s Cooperative Principle and conversational implicatures in Prabowo Subianto’s speech at the 2025 United Nations General Assembly, focusing on their role in constructing diplomatic meaning and ideological positioning. Drawing on Grice’s (1975) Cooperative Principle and Levinson’s (2022) theory of implicature, the research employed a qualitative descriptive design within a pragmatic discourse analysis framework. The data consisted of ten strategically selected utterances containing significant pragmatic features. The findings reveal that the speaker predominantly observes the maxims of Quality and Relation to establish credibility, relevance, and moral commitment to global issues. Meanwhile, the maxims of Manner and Quantity are strategically flouted to convey implicit criticism, ideological stance, and diplomatic politeness. Two types of implicatures were identified: generalized and particularized. Generalized implicatures reflect universal values such as peace, justice, and humanitarian solidarity, whereas particularized implicatures signal Indonesia’s political alignment and long-standing foreign policy orientation. The interplay between cooperative strategies and implicature enhances persuasive communication without direct confrontation. This study demonstrates that pragmatic strategies in diplomatic discourse function not only to construct meaning but also to project national identity and moral authority in contemporary political communication.